Structure of Sr-Zr-bearing perrierite-(Ce) from the Burpala Massif, Russia. (December 2014) - Stachowicz, Marcin; Bagiński, Bogusław; Macdonald, Ray; Kartashov, Pavel M.; OzięBło, Artur; Wożniak, Krzysztof
Abstract: Sr- and Zr-bearing perrierite-(Ce) occurring in aegirinized syenite pegmatites of the Burpala massif, Russia, is compositionally intermediate between perrierite-(Ce) and hezuolinite and occupies a compositional gap in minerals of the chevkinite group. Its crystal structure has been determined using a single-crystal diffractometer fitted with a CCD detector and MoKα X-ray radiation. The mineral is monoclinic; a = 13.815(1), b = 5.668(1), c = 11.842(1) Å, β = 113.843(3)º, V = 848.18(4) Å 3, space group C2/m, Z = 2. The crystal structure was refined with the occupancies [(Ce1.2 La1.0 Nd0.15 ) (Sr1.0 Ca0.5 Na0.15 )]4 (Zr0.5 Fe0.3 Mn0.2 )(Ti1.3 Fe0.7 )2 Ti2 (Si2 O7 )2 O8 on the basis of chemical composition although the allocation of cations to particular sites was performed on the basis of the number of refined electrons in each unique site. The dominance of Zr in the B site links the Burpala perrierite-(Ce) to more Sr-Zr-rich members of the chevkinite group, such as hezuolinite and rengeite. As in all of the perrierite members, there is a distortion of the D site octahedra, which is interpreted as due to the packing of the REE ions.